Influence of videogames and musical instruments on performances at a simulator for robotic surgery. Issue 3 (4th May 2017) - Moglia, Andrea; Perrone, Vittorio; Ferrari, Vincenzo; Morelli, Luca; Boggi, Ugo; Ferrari, Mauro; Mosca, Franco; Cuschieri, Alfred
Abstract: Objective: To assess if exposure to videogames, musical instrument playing, or both influence the psychomotor skills level, assessed by a virtual reality simulator for robot-assisted surgery (RAS). Materials and methods: A cohort of 57 medical students were recruited: playing musical instruments (group 1), videogames (group 2), both (group 3), and no activity (group 4); all students executed four exercises on a virtual simulator for RAS. Results: Subjects from group 3 achieved the best performances on overall score: 527.09 ± 130.54 vs. 493.73 ± 108.88 (group 2), 472.72 ± 85.31 (group 1), and 403.13 ± 99.83 (group 4). Statistically significant differences ( p < .05) between group 3 and group 4 were found for overall score ( p = .009) and for time of completion ( p = .044). As regards experience with the piano, subjects from group 3 outperformed those from group 1 on overall score (496.98 ± 122.71 vs. 470.25 ± 92.31), but without statistically significant difference ( p = .646). Conclusions: The present study suggests that the level of psychomotor skills in subjects exposed to both musical instrument playing and videogames is higher than that in those practicing either one alone. The effect of videogames appears negligible in individuals playing the piano.